1970
DOI: 10.3126/narj.v4i0.4870
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Heritability in Sugarcane

Abstract: Thirty-two genotypes were evaluated in a replicated trial at Sugarcane Research Program, Jitpur, Bara, Nepal in 2000-2001 to estimate phenotypic and genotypic coefficients of variation, heritability and genetic advance for seven stalk characters in sugarcane (Saccharum officinarum L). Analysis of variance revealed highly significant differences between genotypes for all the characters studied. Genotypic variance was higher than environmental one for cane yield, millable cane number, single cane weight, stalk d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
36
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(59 citation statements)
references
References 2 publications
21
36
0
2
Order By: Relevance
“…Qualitative trait MTAs do have the advantage, as they show a lesser degree of missing heritability compared to that of markers associated with quantitative traits. A negative correlation between sucrose content and number of millable canes (NMCs) has been reported in previous studies (Chaudhary 2001). In this study, NMCs showed the highest GCV value which reinforced the strong potential of this trait for improvement through traditional breeding approaches.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Qualitative trait MTAs do have the advantage, as they show a lesser degree of missing heritability compared to that of markers associated with quantitative traits. A negative correlation between sucrose content and number of millable canes (NMCs) has been reported in previous studies (Chaudhary 2001). In this study, NMCs showed the highest GCV value which reinforced the strong potential of this trait for improvement through traditional breeding approaches.…”
Section: Discussionsupporting
confidence: 86%
“…In general, the converted score of qualitative traits showed no variation over the years indicating their stability and low environmental influence on the expression of these traits. Such low environmental influence has also been reported by Chaudhary (2001) and this could be attributed to strictly clonal multiplication of sugarcane. The phenotyping data of sugarcane varieties for nine quantitative traits revealed significant correlations among the traits like internode diameter, plant height and leaf blade width, which are significant contributors to the total cane yield.…”
Section: Discussionsupporting
confidence: 76%
“…Traits exhibiting relatively high GCV estimates may respond favorably to selection. Reference [16] reported high GCV for single stalk weight and millable cane. Genotype × Environment (G × E) interactions are a serious concern in breeding programs as they affect selection decisions.…”
mentioning
confidence: 99%
“…These results indicate that a negligible role was played by the environmental factors in the inheritance of these characters in sugarcane except in single stalk weight character. The high genotypic variance for number of millable cane and stalk length was reported also by (Chaudhary 2001). Singh et al (1996) obtained lowest estimates of cane diameter.…”
Section: I-variability In Traits Of Studied Germplasm 1-genotypic Andmentioning
confidence: 82%